Dose tailoring of adjuvant chemotherapy for breast cancer based on hematologic toxicities: further results from the prospective PANTHER study with focus on obese patients. (24th October 2018) - Matikas, A; Foukakis, T; Moebus, V; Greil, R; Bengtsson, N -O; Steger, G G; Untch, M; Johansson, H; Hellström, M; Malmström, P; Gnant, M; Loibl, S; et al.
Abstract: Background: Adjuvant chemotherapy (ACT) for breast cancer improves relapse-free survival (BCRFS) and overall survival. Differences in terms of efficacy and toxicity could partly be explained by the significant interpatient variability in pharmacokinetics which cannot be captured by dosing according to body surface area. Consequently, tailored dosing was prospectively evaluated in the PANTHER trial. Patients and methods: PANTHER is a multicenter, open-label, randomized phase III trial which compared tailored, dose-dense (DD) epirubicin/cyclophosphamide (E/C) and tailored docetaxel (D) (tDD) with standard interval 5-fluorouracil/E/C and D. The primary end point was BCRFS and the primary efficacy analysis has been previously published. In this secondary analysis, we aimed to retrospectively explore the concept of dose tailoring. Our two hypotheses were that BCRFS would not vary depending on the cumulative administered epirubicin dose; and that dose tailoring would lead to appropriate dosing and improved outcomes for obese patients, who are known to have worse prognosis and increased toxicity after DD ACT. Results: Patients treated with tDD had similar BCRFS regardless of the cumulative epirubicin dose ( P  = 0.495), while obese patients in this group [body mass index (BMI) ≥30] had improved BCRFS compared with nonobese ones (BMI <30) [hazard ratio (HR) = 0.51, 95% confidence interval (CI) 0.30–0.89, P  = 0.02]. Moreover, tDD was associated with improved BCRFS compared with standard treatment only in obese patients (HR = 0.49, 95% CI 0.26–0.90, P  = 0.022) but not in nonobese ones (HR = 0.79, 95% CI 0.60–1.04, P  = 0.089). The differences were not formally statistically significant ( P for interaction 0.175). There were no differences in terms of toxicity across the epirubicin dose levels or the BMI groups. Conclusions: Dose tailoring is a feasible strategy that can potentially improve outcomes in obese patients without increasing toxicity and should be pursued in further clinical studies. ClinicalTrials.gov identifier: NCT00798070.